Influencia del Bacillus subtilis en la sanidad y desarrollo de la mazorca de cacao (Theobroma cacao L.), en sus primeros tres estadios, en la zona de Puebloviejo - Ocaña Baquerizo, Derian Ariel (2020)
Cocoa (Theobrama cacao L.) is currently the third agricultural export item. Its annual production represents 6,7 % of GDP. Among the pathogenic microorganisms that affect various cocoa crops are fungi. They are among the main causes of damage and deterioration of certain plantations. In experimental studies it has been possible to determine the antifungal effect that the Bacillus subtilis bacterium has to release some substances with the capacity to break the cell walls of other organisms by causing their lysis. The objective of the research was to evaluate the influence of Bacillus subtilis on the health and development of the cocoa pod, in its first three stages, in the Puebloviejo area, whose work was carried out on the grounds of the Las Cañitas farm, located in km 4.5 on the Puebloviejo - Ventanas road, Los Ríos province. The planting material used was the clone “CCN-51” of 3 years of planting, it was distributed in eight treatments and three repetitions, for which the design of complete random blocks was used with the Tukey test at 5% significance. Among the variables used were: ears formed est. 1, ears formed est. 2, formed ears 3, fallen ears, black ears, diseased ears est. 3 (mycelium) and finally healthy ears are. 3. The recorded results expressed that the application of Bacillus subtilis at a dose of 2 lt / ha in stage 2 of the ear, showed the best results and directly influenced to obtain the highest values in the variables of number of ears stage 2, ears. in stage 3, healthy ears are 3 and lower averages in the variables of fallen ears, black ears and diseased ears stage 3 (mycelium). In the same way, the treatment that presented the highest economic income according to the largest number of healthy ears in stage 3, was generated with the application of Bacillus subtilis in a dose of 2 lt / ha in stage 2 of the ear.